PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA PERUSAHAAN SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG LISTING DI BURSA EFEK INDONESIA 2012 - 2014) - BAKUH KARYANTO (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2015)
The purpose of this study was to determine the effect of intellectual capital toward firm value with the financial performance as the intervening variable.The independent variable applied in this study was the intellectual capital which was measured by value added intellectual coefficient (VAIC). The dependentvariable in this study was the firm value is measured by using price-to-book value (PBV), while financial performance as an intervening variable is measured by using return on asset (ROA). The samples of this study were the banking companies listed by the Indonesia Stock Exchange (IDX) within the period of 2012-2014. Data were collected by using purposive sampling method. Based on the mentioned criteria, 27 companies were selected as the sample of this study. The data analysis tool used in this study was path analysis with SPSS software 21 version.